ANALISIS PEMENUHAN AIR BERSIH DI DAERAH CEKUNGAN AIR TANAH - Rifai, Muji; Wahyudi, Agus Hari; Ywangtini, Hendriana (Prodi Teknik Sipil Fakultas Teknik Universitas Sebelas Maret Surakarta, 2025)
Population and economic growth have significantly increased human demand for clean water, both in terms of quantity and quality. One way to meet this growing demand is through the extraction of groundwater. This study aims to analyze the fulfilment of clean water needs in the city of Salatiga, which is located within the Rawapening and Salatiga Groundwater Basins. The study emphasizes the importance of sustainable water resource management to ensure future water availability. Using a qualitative descriptive approach, the research was conducted through literature review, field surveys, geoelectrical measurements, hydrological analysis, and the development of a water balance assessment. The results indicate that the available groundwater potential is approximately 5 m³/second, while current utilization is only around 0.069 m³/second. Analysis of domestic and non-domestic water demand reveals an increasing trend through 2028 in line with population growth. The water balance analysis shows seasonal fluctuations, with both surplus and deficit periods. A water deficit occurs during eight months (May to December), with the highest shortfall recorded in October (397 liters/second) and the lowest in May (23 liters/second). To address this shortfall, groundwater resources are proposed as an alternative solution. Given Salatiga's location within a groundwater basin, the city possesses considerable groundwater potential. This presents an opportunity for clean water provision through the development of deep wells, guided by the recommendations from geoelectrical surveys (both in terms of location and potential), to ensure optimal water yield for meeting clean water demands.